EEffects of nano-curcumin and curcumin on the oxidant and antioxidant system of the liver mitochondria in aluminum phosphide-induced experimental toxicity - Akram Ranjbar; Leila Gholami; Hassan Ghasemi; Nejat Kheiripour (Nanomedicine Journal, 2020)
Objective(s): Aluminum phosphide (AlP) is commonly used pesticide which could cause poisoning mainly through the induction of oxidative stress. The present study aimed to evaluate the effects of nano-curcumin and curcumin on the oxidant and antioxidant system in the liver mitochondria using AIP-induced toxicity model. Materials and Methods: In this study, 36 male albino Wistar rats were randomly divided into six groups (n=6). The control subjects and animals poisoned with AlP (2 mg/kg) received treatment with and without nano-curcumin (100 mg/kg) and curcumin (100 mg/kg) for seven days. Mitochondria were isolated from the liver and analyzed in terms of lipid peroxidation (LPO), total antioxidant capacity (TAC), total thiol groups (TTGs), superoxide dismutase (SOD), and catalase activity. In addition, mitochondrial viability was assessed. Results: AlP caused a significant increase in the LPO levels, while significantly decreasing TAC, TTG, SOD, catalase activity, and mitochondrial viability compared to the controls (P<0.05). Moreover, nano-curcumin treatment significantly enhanced TAC, TTG, SOD, and mitochondrial viability (P<0.05). Curcumin could also improve TTG and mitochondrial viability (P<0.05). Conclusion: According to the results, nano-curcumin exerted protective effects against AlP-induced experimental toxicity, and the effect was attributed to the antioxidant properties of this compound.